Representing language, culture and citizenship to minoritised ethnic groups: the teaching of Mandarin Chinese to Mongolian learners as a second language in China since 1912 - Wu, Jiaye (2022)
My PhD study investigates the under-researched history of teaching Mandarin Chinese as a second language to Mongolian learners within China since 1912, and its implications for the present day. This research makes a novel contribution to understanding how a national language and national identities are promulgated to a minoritised ethnic group over time. Mandarin teaching to Mongolian learners is revealed as a site where different representations of the Chinese nation contest and negotiate with one another, shaped by the power relations between Mongolian and Han. I employ critical discourse analysis to examine a wide range of Mandarin Chinese language textbooks for Mongolian learners issued by the Republican (1912-1949) and People’s Republic of China’s governments (1949-present) to explore the changes in expectations of Chinese cultural knowledge and values to be taught, in particular in terms of Chinese history and citizenship. The findings show that the Chinese cultural knowledge and values conveyed through the textbooks is given different emphases at different times, but it frequently serves as a tool serving the interests of the governments to reproduce official understandings of Chinese national identities, with Mongolian cultural features being often neutralised and/or made subservient to Han-dominant Chinese national values. In addition, to explore how the dominance of Han culture and values in the textbooks has been embraced and/or challenged by Mongolian elites in the early twentieth century and Mongolian teachers of Mandarin Chinese in the present, two approaches are adopted. First, a historical linguistic analysis of how Mandarin Chinese pronunciation is presented to Mongolians in a dictionary compiled by a Mongolian official named Khaisan in 1917 is conducted, when the basis for a standard Chinese was still being debated. This part of the study reveals that the diverse linguistic sources that Khaisan drew on challenge the monolingual Han native speakership ideology. Second, the historical textual analysis is augmented by data from two months’ field work in Hohhot, Inner Mongolia in 2018. There, I conducted semi-structured interviews, surveys and classroom observations of the Mongolians and Han who work in the field of Mandarin teaching to Mongolian learners to explore their understandings of the Mandarin language and views on what cultural knowledge and values to teach. The data highlight how different views of Mandarin Chinese teaching, as a communicative tool, as linguistic and cultural capital, and as an identity marker, are negotiated by Mongolians today. Looking into the past and present impact of Mandarin Chinese teaching on Mongolian ethnic identity, my work is the first to combine historical textbook analysis, historical linguistics, and ethnography. It makes an important contribution to the field of the History of Language Learning and Teaching, which has thus far been heavily skewed to the history of language education in Europe. Second, it addresses a gap in bilingual education studies, where little attention has been paid to the teaching of the majority language that Mongolians in the past and at present as the actors to define the knowledge of Chinese to teach. Third, my analysis of strategies for incorporating Mongolians into China are relevant to other non-Han studies such as Tibetans and Uyghurs and ethnic minority studies in different political and educational contexts.